Use of Information Communication Technology (ICT) in Library and Information Science Education and Research: A Study of Central Universities in Uttar Pradesh - Lata, Neha; Sonkar, Sharad Kumar (DESIDOC Journal of Library & Information Technology, 2023)
With the advent of advanced technology, ICT has revolutionised the way academics perform their work, helping them to deal with larger datasets and improve the outcomes of their investigations. The main objective of this study article is to obtain a better understanding of how ICT can be used in LIS education and research. For the study, a survey design was used. Out of 303 students and research scholars from BBAU, BHU, and AMU, 179 respondents were chosen using Raosoft (Sample size calculator). The questionnaire was the only data collection tool used in both online and offline modes. Microsoft Excel was used to analyse the responses. The study’s findings showed that most students and research scholars use ICT tools in their education and research work. This study also focuses on integration regarding the use of information and communication technology, as well as what may improve the status of the education and research sectors by using ICT and how ICT can help in stress reduction in various aspects among students and research scholars. Students and research scholars would benefit from the study because it would contribute to scholarly research and fill a gap in the literature on the use of information and communication technologies.